1971. A Randomized, Double-Blind, Placebo-Controlled Trial to Assess the Safety and Tolerability of a Respiratory Syncytial Virus (RSV) Neutralizing Monoclonal Antibody (MK-1654) in Healthy Subjects. (26th November 2018) - Aliprantis, Antonios; Wolford, Dennis; Caro, Luzelena; Maas, Brian; Ma, Hua; Vora, Kalpit; Geng, Dong; Railkar, Radha; Lee, Andrew; Sterling, Laura; Lai, Eseng
Abstract: Background: Respiratory syncytial virus (RSV) is the most common cause of lower respiratory tract infection and hospitalization in infants. Prophylaxis for RSV infection is only recommended for the highest risk infants, leaving the majority of infants unprotected. MK-1654 is a fully human monoclonal antibody targeting the RSV fusion (F) protein with Fc domain mutations to extend half-life that is being developed to provide passive immunity against RSV in infants. The safety profile, development of anti-drug antibodies (ADAs), serum neutralizing antibody (SNA) titers, and pharmacokinetics (PK) in healthy adult volunteers receiving single-ascending doses of MK-1654 was evaluated. Methods: In this double-blinded ongoing Phase 1 study, healthy adults of non-childbearing potential (19 to 59 years) were randomized in a 3:1 ratio to receive a single dose of MK-1654 or placebo (0.9% sodium chloride injection, USP) as a bolus intramuscular injection (IM) or in an intravenous infusion (IV) for at least 2.5 hours. Dose levels included 100 and 300 mg IM, and 300, 1, 000, and 3, 000 mg IV. Standard methods were used to assess safety and tolerability. Serum was tested for ADAs and RSV A SNA titers at time points up to day 120 and up to day 90, respectively. MK-1654 adult PK and estimated PK for infants will be reported separately. Results: A total of 152 subjects (male = 117, female = 35) have been enrolled (mean age = 41 years). No deaths, serious adverse events, discontinuations due to AEs, clinically significant laboratory AEs, or dose-dependent pattern of drug-related AEs were reported. Sixty-six subjects reported 181 clinical AEs (97.8% mild and 2.2% moderate in intensity). The most common AEs (≥5%) were headache, nasal congestion, vessel puncture site hemorrhage, oropharyngeal pain, rhinorrhea and nausea. No treatment emergent ADAs have been identified through time points tested. Administration of MK-1654 resulted in a dose-dependent increase in RSV A SNA titers through Day 90 (figure). Updated safety, SNA titers and ADAs will be provided. Conclusion: MK-1654 was generally well tolerated at doses up to 300 mg IM and up to 3, 000 mg IV and resulted in a dose-dependent increase in SNA titers, reflecting biologically active MK-1654 in the serum. No treatment emergent ADAs have been observed. Disclosures: A. Aliprantis, Merck: Employee and Shareholder, Salary and stock options. D. Wolford, Merck: Employee and Shareholder, Salary and stock options. L. Caro, Merck: Employee and Shareholder, Salary and stock options. B. Maas, Merck: Employee and Shareholder, Salary and stock options. H. Ma, Merck: Employee and Shareholder, Salary and stock options. K. Vora, Merck: Employee, Salary. D. Geng, Merck: Employee and Shareholder, Salary and stock options. R. Railkar, Merck: Employee and Shareholder, Salary and stock options. A. Lee, Merck: Employee and Shareholder, Salary and stock options. L. Sterling, Merck: Investigator, Research grant. E. Lai, Merck: Employee and Shareholder, Salary and stock options.